invariant Natural Killer T cell therapy as a novel therapeutic approach in hematological malignancies - Boonchalermvichian, Chaiyaporn; Yan, Hao; Gupta, Biki; Rubin, Anabel; Baker, Jeanette; Negrin, Robert S. (Frontiers in Transplantation, 2024)
Invariant Natural Killer T cell therapy is an emerging platform of immunotherapy for cancer treatment. This unique cell population is a promising candidate for cell therapy for cancer treatment because of its inherent cytotoxicity against CD1d positive cancers as well as its ability to induce host CD8 T cell cross priming. Substantial evidence supports that iNKT cells can modulate myelomonocytic populations in the tumor microenvironment to ameliorate immune dysregulation to antagonize tumor progression. iNKT cells can also protect from graft-versus-host disease (GVHD) through several mechanisms, including the expansion of regulatory T cells (Treg). Ultimately, iNKT cell-based therapy can retain antitumor activity while providing protection against GVHD simultaneously. Therefore, these biological properties render iNKT cells as a promising “off-the-shelf” therapy for diverse hematological malignancies and possible solid tumors. Further the introduction of a chimeric antigen recetor (CAR) can further target iNKT cells and enhance function. We foresee that improved vector design and other strategies such as combinatorial treatments with small molecules or immune checkpoint inhibitors could improve CAR iNKT in vivo persistence, functionality and leverage anti-tumor activity along with the abatement of iNKT cell dysfunction or exhaustion.